A clinical method for physicians in palliative care: the four points of agreement vital to a consultation; context, issues, story, plan. Issue 3 (19th November 2013) - Noble, Bill; George, Rob; Vedder, Rachel
Abstract : In palliative care, where interactions cross clinical, pathological, psychological, social and spiritual considerations, it may be useful to take a minimal approach and avoid an overcomplicated or formulaic structure for the consultation. We will concern ourselves with points in the encounter where doctor and patient with or without family or carers need to be in agreement. Whether a consultation is based on a structured interview, a cue-based assessment or a narrative approach, the points of agreement or concordance need to cover four key areas; missing any of these has grave consequences for the clinical relationship. Without concordance, patients may be right to conclude that you don't know why you're all there (context), you don't know what's the matter (issues), you don't know what's going on (story) or you don't know what you're doing (plan). These four elements may serve also as a guide to the quality and effectiveness of an encounter among a doctor, patient and carers. We consider how this clinical method might integrate the nosological practices of doctors in palliative care services better, and we argue that finding concordance is likely to establish a better doctor–patient relationship at a human and professional level through empathy and trust rather than just a technical exchange.